1985
DOI: 10.1099/0022-1317-66-12-2685
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal for Naming Adenovirus Genome Types, Exemplified by Adenovirus Type 6

Abstract: SUMMARYA numerical code to denominate adenovirus (AV) genome types is proposed. Seven restriction endonuclease patterns are listed in alphabetical order (BamHI, BglII, BstEII, EcoRI, HindIII, KpnI, Sinai); patterns deviating from those of the prototype (1) are named 2, 3 etc. depending on the chronological order of the respective isolates. Thus AV6/3 : 12 31121 is a type 6 strain deviating from the prototype in three patterns, i.e. those of BgllI, BstEII and KpnI. From 24 AV6 isolates, six were identical with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 9 publications
2
38
0
Order By: Relevance
“…In this study, characterization of species C isolates into serotypes identified types AdV-1, AdV-2, and AdV-5 in both IS and non-IS cases, with no significant differences identified between the groups. AdV-6 was absent as also noted in other studies (2,3).…”
supporting
confidence: 63%
See 2 more Smart Citations
“…In this study, characterization of species C isolates into serotypes identified types AdV-1, AdV-2, and AdV-5 in both IS and non-IS cases, with no significant differences identified between the groups. AdV-6 was absent as also noted in other studies (2,3).…”
supporting
confidence: 63%
“…Interestingly, five of six genetic types identified were present in ISassociated strains, while only three types were present in the non-IS-associated strains. This large genetic diversity is supported by previous analysis of species C serotypes in non-ISassociated isolates (1,2). Despite this strain diversity, D2 was shown to be the dominant genome type in both IS-and non-IS-associated adenovirus isolates.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…For example, a comparison between 24 AV6 isolates and the AV6 prototype has revealed percentages of comigration between 65 ~ and 100 ~ (Adrian et al, 1985b). Between two different AV species from subgenus D, have found percentages of comigration between 38 ~o and 79 ~.…”
Section: Short Communicationmentioning
confidence: 99%
“…To decide between these two possibilities, viruses isolated early and late after infection were compared by DNA restriction analysis. In this context it is advantageous that adenoviruses of subgenus C (types 1, 2, 5, 6) display a high degree of genetic variability (Adrian, Best & Wigand, 1985; Fig. 3.…”
mentioning
confidence: 99%